Wernicke Encephalopathy Presenting in a Patient with Severe Acute Pancreatitis - Arana-Guajardo, Ana Cecilia; Cámara-Lemarroy, Carlos Rodrigo; Rendón- Ramírez, Erick Joel; Jáquez-Quintana, Joel Omar; Góngora -Rivera, Juan Fernando; Galarza-Delgado, Dionicio Ángel (JOP. Journal of the Pancreas, 2012)
<!–[if gte mso 9]> Normal 0 14 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Tabella normale"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400; –> <!–[endif] –> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Arial Unicode MS"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: HI; mso-bidi-language: HI;" lang="EN-US">Context<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Arial Unicode MS"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: HI; mso-bidi-language: HI; mso-bidi-font-weight: bold;" lang="EN-US"> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Arial Unicode MS"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: HI; mso-bidi-language: HI;" lang="EN-US">Acute pancreatitis can lead to prolonged fasting and malnutrition. <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: HI; mso-bidi-language: HI;" lang="EN-US">Many metabolic changes, including <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Arial Unicode MS"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: HI; mso-bidi-language: HI;" lang="EN-US">thiamine deficiency, may lead to the well know pancreatic encephalopathy. In this condition however the thiamine deficiency is rarely suspected. Case report We report the case of a 17-year-old woman with severe acute pancreatitis who developed mental status changes and ophthalmoplegia. A magnetic resonance image showed hyperintensive signals in periventricular areas, medial thalamus, and mammillary bodies, findings consistent with the diagnosis of Wernicke encephalopathy. Thiamine treatment reversed neurological complications. Conclusion Wernicke encephalopathy secondary to thiamine deficiency should be considered as a possible cause of acute mental status changes in patients with acute pancreatitis and malnutrition. Prophylactic doses of thiamine could be considered in susceptible patients.